Tourist Preferences for Seamount Conservation in the Galapagos Marine Reserve - Ison, Sierra; Ison, Theo; Marti-Puig, Patricia; Needham, Katherine; Tanner, Michael K.; Roberts, J. Murray (Frontiers in Marine Science, 2021)
Seamounts provide oases of hard substrate in the deep sea that are frequently associated with locally enhanced biological productivity and diversity. There is now increasing recognition of their ecological and socio-economic importance. However, management strategies for these habitats are constrained not only by limited ecological understanding but by the general public’s understanding of the pressures facing these ecosystems. This study adds to the growing literature on willingness to pay for conservation of deep-sea ecosystems and species by undertaking a stated preference survey to assess tourist’s awareness of seamounts and their preferences for protection within the Galapagos Marine Reserve. Visitors' perceptions of seamount biodiversity must be studied because tourists are key drivers of the Galapagos economy and account for 41% of the Marine Reserve budget. Our survey captured the attitudes, perceptions and willingness to pay of tourists for an increase in the entrance fee to the Galapagos Marine Reserve. Results showed tourists were willing to pay on average US$48.93 in addition to existing entrance fees. The results of this study support the willingness to develop a multiuse management plan for the Galapagos Marine Reserve, balancing conservation, local communities livelihoods and sustainable tourism. Our results evidence a willingness to support and fund conservation, which is of critical importance to both the Galapagos National Park and local non-governmental organisations heavily reliant for their work on entrance fees and donations respectively. Overall, the conclusion from this study is that, despite limited knowledge, visitors of the Galapagos Islands attach positive and significant values to the conservation of seamount biodiversity.